(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article analyzes the foreign experience of implementing the tax administration of large taxpayers, as a result of this analysis, issues of improving the tax legislation of the Republic of Uzbekistan, a proposal for further improvement of the tax administration of large taxpayers and recommendations are developed.